HUBUNGAN PERIODE LAKTASI DENGAN PRODUKSI SUSU SAPI PERAH PERANAKAN FRIES HOLLAND (PFH) DI BALAI BESAR PELATIHAN PETERNAKAN BATU - Marsalis, Yohanes; Marhaeniyanto, Eko; Suharto, Kresno (Fakultas Pertanian, 2018)
This study aims to determine the relationship between lactation period and milk dairy cattle production with the material used is Fries Holland (PFH) dairy cows as many as 20 heads which are lactation both 12 heads, third lactation 3 heads, and fourth lactation 5 heads. The research method is field survey with the data obtained is to follow and record the amount of milk in milking process every lactation period. With the observed variables is the amount of milk production each lactation period, age, environment, feeding and disease prevention, then the existing data were analyzed using simple linear regression analysis with SPSS program statistic version 17.0. Results of this study the average production of milk dairy cows is highest in the second lactation and decreased in the third and fourth lactation sequentially ie 11.26 liters/head/day, 10.00 liters/head/day and 8.88 liters/head/day. The lactation period (lactation 2-4) had significant effect (P